Formation of future policeman professional communication competences by the means of the ukrainian language - Голопич, І. М. (Scientific notes of the pedagogical department, 2019)
The article contents the analysis of the scientific approaches to defining and grouping of the future professionals’ competences on the basis of which is being built the actual understanding of the notion “professional communication competences of the policeman”. The aim of the article is to take the point of the notion “professional communication competences of the policeman”, selection of the means of Ukrainian language due to which are forming the forenamed competences in the higher education institutions with specific learning conditions. Is defined the essence of the notion “professional communication competences of the policeman” as a capacity of law enforcement employees to get in touch with the victim and the delinquent, readiness to define the reasons and motivation of the action of the law breakers, ability to resolve conflicts and to ensure security of the person, inclination to self-regulation and self-control when interacting with offenders. Professional communication competences are groped as follows: motivative and analytical (the interest to partnership in the professional activity, the ability to analyze the causes and interferences of the successful professional communication), cognitive and legal (knowledges and skills of professional communication on a legal basis), estimative and corrective competences (skills of reasonable self-esteem and self-control, skills of self-correction in the actions and behaviour, positively change themselves). The matter of the forenamed competences is much wider comparing to communication competence, because they content the ability of cooperation in partnership, ability of teamwork and to show the leader qualities, the readiness for positive self-changes, to show and develop the professional potential. To the means of Ukrainian language are ascribed both means of linguistic character – lexis, phraseology, grammar, syntax, and methodic tools – exercises, lexicography. The research methods are: scientific literature analysis on the defined topic, educational and professional programs of the policeman training, work program on academic discipline “Ukrainian language of the professional orientation”, questioning of teachers, cadets, part-time students, analysis of the questioning results. Practical significance is the described by the author exercises aimed to the formation of professional communication competences of the future policeman by the means of Ukrainian language. The perspectives of the future research lie in the development of the elective special course “Theory and practice of policeman professional communication” for teachers and cadets.